Treatment of Patent Ductus Arteriosus with Cyclo-oxygenase Inhibitors beyond 2 Weeks of Age in Very Low Birth Weight Infants - Lainwala, Shabnam; Hussain, Naveed (American Journal of Perinatology, 2016)
Background Cyclo-oxygenase inhibitors (COX-I) treatment of patent ductus arteriosus (PDA) in very low birth weight (VLBW) infants during the early postnatal period is well established, but their use beyond early postnatal period is not well studied.Objective The objective of this study was to determine the effectiveness of postnatal COX-I for PDA treatment beyond 2 weeks of age in VLBW infants.Study Design A retrospective cohort of VLBW infants admitted to two tertiary NICUs between 1990 and 2008 were studied. Infants with symptomatic PDA were treated with COX-I and infants with failed medical treatment were candidates for surgical ligation. Effectiveness of COX-I treatment, measured by the need for surgical ligation, was compared between early (day of life [DOL] < 14, early treatment group [ETG]) and late (DOL ≥ 14, late treatment group [LTG]) treatment groups.Results Of the 1,289 infants with PDA, 1,082 (84%) were treated with COX-I; 1,046 (97%) infants were in ETG and 36 (3%) in LTG. PDA ligation rates after COX-I treatment were 15% in ETG and 14% in LTG (p-value: not significant). There were no significant differences in demographics or morbidities between the two groups.Conclusions In VLBW infants, late treatment of PDA with COX-I was as effective as early treatment. Trial of late COX-I treatment is warranted for symptomatic PDA before surgical treatment.
Keywords: patent ductus arteriosus; COX inhibitor; treatment; PDA ligation; premature infant